Prescribing pattern for acute diarrhea in children: A survey of pediatricians from Maharashtra, India - Vikram S Patra; Jeetendra B Gavhane; Priyanka S Amonkar (Wolters Kluwer Medknow Publications, 2022)
Context: Irrational use of medications for acute diarrhea in children is rampant. We conducted this survey to analyze prescription practices among pediatricians for acute diarrhea and their deviation from standard treatment guidelines. Subjects and Methods: A self-administered online questionnaire regarding prescription practices was circulated among pediatricians in Maharashtra, India, through various academic groups on WhatsApp, during the World Oral Rehydration Salt (ORS) Week, 2021. The questionnaire was anonymous and consisted of 15 compulsory close-ended multiple-choice questions. Results: Two hundred and eighty-seven pediatricians participated. Among which, 88.9% of the participants said that they prescribed ORS in acute diarrhea, 26.8% preferred zinc supplementation only in the case of watery diarrhea, 62% used probiotics or probiotics plus zinc combinations, and 60% said that they prescribe antisecretory drugs such as racecadotril. Forty percentage of the participants admitted that they occasionally use antibiotics for the management of acute diarrhea, while 5% said that they frequently do so. Most pediatricians advise appropriate ORS substitutes. Large number of pediatricians perceived probiotics (51.2%), dietary restriction (15.7%), racecadotril (10.5%), and antibiotics (6.3%) to be an important part in managing acute diarrhea. Only 25.4% of the pediatricians answered correctly and said parental counseling along with zinc and ORS work best as treatment. Conclusions: This study demonstrates low adherence by pediatricians to standard treatment guidelines for the management of acute diarrhea. Misuse of antibiotics and unscientific use of drugs were evidenced from this study. Awareness regarding the advantages of ORS among pediatricians is high. At present, there is a need to focus on appropriate feeding practices, emphasizing on the role of zinc and discouraging use of antibiotics, probiotics, antisecretory drugs, and irrational combinations.